Analysis of the factors influencing the formation of entrepreneurial intention among senior individuals - Shalunova, Tatiana (2018)
This study evaluates the influence of motivational factors among individuals over 50 years old on the formation of their entrepreneurial intention. A thorough analysis of the differences between male and female senior entrepreneurs and opportunity- and necessity-driven motive is important for a full understanding of older entrepreneurs. We analyzed data from the Global Entrepreneurship Monitor between 2009 and 2013 across EU countries. In light with the Theory of Planned Behavior the findings show that perceived behavior control factors have significant and positive effect on entrepreneurial intention, while subjective norms have no significant effect on senior entrepreneurs. The perception of behavioral control factors differs among the female and male as well as opportunity- and necessity-driven senior entrepreneurs. This suggests that policymakers and business advisory agencies should offer programs that incentivize senior entrepreneurs to seize business opportunities by overcoming the fear of failure and developing a belief in their own entrepreneurial capabilities.